PENGARUH MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMK - dylla rizka amalia; Kartika -; Muhammad Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This study aims to determine the effect of the Problem Based Learning approach through the cooperative learning model of the Team Assisted Individualization (TAI) type, toward the problem solving skills of vocational high school students. The population in this study were all students of SMK Industri Mandiri Karawang, with each 20 selected samples from class X-TKJ and AKA. The instruments used were a test of problem solving skills as many as 5 items. The result of the study show the achievement of problem solving abilities of students who get learning with the Problem Based Learning approach through the cooperative learning model Team Assited Individualization type is better than the class that uses ordinary Problem Based Learning.